Controlled release of microencapsulated probiotics in food matrix - Basu, Soham; Banerjee, Debolina; Chowdhury, Ranjana; Bhattacharya, Pinaki (Journal of food engineering, 2018)
The present study focusses on direct entrapment, internal and external microencapsulation of Lactobacillus casei (L. casei) in bio-polymer (alginate) matrix and their performance in lactose-rich media. Probiotic beads and microcapsules were suspended in modified de Mann-Rogosa-Sharpe (MRS) medium containing lactose and a refreshing drink-green coconut water, fortified with the same carbohydrate. A novel mathematical model has been developed to simulate substrate and biomass time-concentration profiles as a function of radial position within the probiotic beads/capsules. Further, using the burst-release mechanism, the model could also predict the release time of L. casei-868 min, 587 min and 574 min from alginate beads, external and internal microcapsules respectively. The predicted values were in good agreement with the experimental results for both modified MRS medium and coconut water. The release time of probiotics∼10 h indicates the scope for potential application of probiotic beads/capsules in the production of probiotic functional health drinks using green coconut water. •Model designed to simulate substrate diffusion, biomass growth in microspheres/beads.•Substrate permeation to microcapsule/bead interior controlled by reaction-diffusion.•Significant time-lag attained prior to release of probiotics in food matrix.•Burst-release time maximum for direct entrapment, least for internal gelation.